Mengenal Konsep Zero Waste : Mengurangi, Mendaur Ulang, Dan Mengelola Sampah Dengan Bijak - Novianti, Rina Dian; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Waste management through the implementation of the zero waste concept is an initiative that involves a transformation of innovative and efficient lifestyles, aiming to promote a renewable resource cycle. This article comprehensively discusses the Zero Waste concept with a literature study approach, delving into strategies for reducing, recycling, and wisely managing waste. Through the analysis of various literature sources, the article outlines the core principles of Zero Waste, including the crucial understanding of waste separation at the household level, composting, and the collection of items suitable for resale. This concept goes beyond being merely a waste management method; it is also a philosophy that encourages a shift in societal perspectives on waste, considering it as a valuable resource. It is hoped that the in-depth understanding of the Zero Waste concept presented in this article will provide a foundation for everyone to adopt environmentally friendly practices, minimize waste, and contribute to global environmental protection.